Confidence intervals for a two-parameter exponential distribution: One- and two-sample problems. Issue 4 (16th February 2018) - Krishnamoorthy, K.; Xia, Yanping
ABSTRACT: The problems of interval estimating the mean, quantiles, and survival probability in a two-parameter exponential distribution are addressed. Distribution function of a pivotal quantity whose percentiles can be used to construct confidence limits for the mean and quantiles is derived. A simple approximate method of finding confidence intervals for the difference between two means and for the difference between two location parameters is also proposed. Monte Carlo evaluation studies indicate that the approximate confidence intervals are accurate even for small samples. The methods are illustrated using two examples.